Optimal design of a modular axial‐flux permanent‐magnet synchronous generator for gearless wind turbine applications - Seyed Ataollah Ashrafzadeh; Ali Asghar Ghadimi; Ali Jabbari; Mohammad Reza Miveh (Wind Energy, 2024)
Abstract Air‐cored axial‐flux permanent‐magnet synchronous generators (AFPMSGs) are potential candidates for gearless direct‐coupled wind turbines (DCWTs) owing to providing high efficiency and power density. The design of a DCWT generator is so complicated since the generator cost, dimension, and weight affected by gear elimination. Therefore, it is essential to find an optimal AFPMSG design at rated conditions. In this paper, an accurate procedure for the optimal design of an air‐cored AFPMSG applicable for DCWTs is proposed. The genetic algorithm (GA) is used for multi‐objective design optimization to reach the optimal configuration as well as system dimension in order to decrease the weight, increase the power density and enhance the effectiveness of the generator. To validate the efficiency of the suggested optimization proceducer, a 30 kW AFPMSG has been considered as a case study. The results of optimization have been investigated by finite element analysis (FEA). A prototype generator is also fabricated, and the test results are offered and compared with the numerical study. The outcomes show that there exists an acceptable agreement between FEA and experimental outcomes with the error percentage about of 1.35%.